Fontes de P de contrastantes solubilidades e formas de aplicação no crescimento inicial do cafeeiro - Marra, Mauro Pinheiro (2021)
Phosphorus (P) is a nonrenewable essential chemical with finite global reserves. Some soils in the Cerrado are strong P drains, so to make them a source of this chemical, large amounts of fertilizer are needed. In this context, this study aimed to verify the responses to associations of P sources with contrasting solubilities in coffee seedlings and evaluate its residual availability by Mehlich 1 and resin extractors. A randomized block design (RBD) with three replications was adopted. The treatments were distributed in a factorial scheme [(5 x 2) + 2]. The first factor consisted of the association of Bayòvar reactive natural phosphate (RNP) and triple superphosphate (TSP) fertilizers in five proportions: 100%:0%; 75%:25%; 50%:50%; 25%:75%; 0%:100% (RNP:TSP). The second factor consisted of how TSP was applied (localized or homogeneous) following an additional Compound Control consisting of the application of organic compost, and Absolute Control, due to the absence of P. Plant characteristics were evaluated: increase in height (Δh), increase in stem diameter (Δd), the number of nodes in plagiotropic branches, dry mass of leaves and tender branches, total dry mass, amount and content of P and Ca. At 92 days after transplanting in two positions in the soil, pH in water, P remnant (P-rem), P Mehlich 1 and P resin were evaluated. The localized application of TSP promoted beneficial changes in the soil with a significant increase in the values of P-rem and P available by Mehlich 1 and resin, and indicate residual power of P available to the seedlings. There were no statistical differences in plant characteristics as a result of P source associations and the way SFT was applied. The 50%:50% ratio with localized TSP showed significant differences at 92 days after transplanting, in plant characteristics, amount, content and nodes in the plagiotropic branches in relation to the Compound Control.